Upper extremity kinematics and body roll during preferred-side breathing and breath-holding front crawl swimming - Payton, C. J.; Bartlett, R. M.; Baltzopoulos, V.; Coombs, R. (Journal of Sports Sciences, 1999)
Front crawl swimmers often restrict the number of breaths they take during a race because of the possible adverse effects of the breathing action on resistance or stroke mechanics. The aim of this study was to determine whether differences exist in the kinematics of the trunk and upper extremity used during preferred-side breathing and breath-holding front crawl swimming. Six male swimmers performed trials at their 200 m race pace under breathing and breath-holding conditions. The underwater arm stroke was filmed from the front and side using video cameras suspended over periscope systems. Video recordings were digitized at 50 Hz and the three-dimensional coordinates of the upper extremity obtained using a direct linear transformation algorithm. Body roll angles were obtained by digitizing video recordings of a balsa wood fin attached to the swimmers' backs. The swimmers performed the breathing action without any decrement in stroke length (mean +/- s: breathing 2.24 +/- 0.27 m; breath-holding 2.15 +/- 0 0.22 m). Stroke widths were similar in the breathing (0.28 +/- 0.07 m) and breath-holding (0.27 +/- 0.07 m) trials, despite swimmers rolling further when taking a breath (66 +/- 5 degrees) than when not (57 +/- 4 degrees). The timing of the four underwater phases of the stroke was also unaffected by the breathing action, with swimmers rolling back towards the neutral position during the insweep phase. In conclusion, the results suggest that front crawl swimmers can perform the breathing action without it interfering with their basic stroke parameters. The insweep phase of the stroke assists body roll and not vice versa as suggested in previous studies.